The motivation and capability to job craft - Beer, Lynn (Kansas State University, 2016)
For decades psychologists have studied ways in which organizations can redesign jobs to achieve improved performance and worker satisfaction. Recently there has been interest in job crafting, the process by which workers themselves change their jobs to achieve similar ends. This study examined the relationships between job crafting and (a) worker autonomy and (b) proactive personality. It was found that both autonomy and proactive personality were positively related to job crafting, with proactive personality being more strongly related to job crafting than was autonomy. Thus, the potential for both situational and individual characteristics to influence job crafting was found.
Keywords: Proactive personality; AutonomyJob crafting